P120 A STRANGE HEART MURMUR. (18th May 2022) - Nunziata, L; Ambrosino, S; Carbone, L; Ruggiero, V; Laezza, A; Prisco, A; Nardiello, V; Miele, R; Terracciano, F; Falato, S; Granata, F; Maresca, G; et al.
Abstract: An 38–year–old man was referred to our hospital for chest pain. He was a smoker but had no other cardiovascular risk factors and had no history of relevant diseases. On cardiovascular examination, a rough grade IV/V systolic murmur was present at the mesocardium. His electrocardiogram showed sinus tachycardia and complete right branch block. On laboratory tests, cardiac biomarkers were negative. A transthoracic echocardiogram showed left ventricle cavity–sized at the upper limits with preserved systolic function and mild concentric hypertrophy. The aortic root was ectatic with tricuspid valve and mild regurgitation. In addition, there was a great spheric cavity in the region of the right sinus of Valsalva that was communicating with the aortic lumen with turbulent flow inside. The Pulmonary Trunk was dilated and there was a strange turbulent flow within it that extended towards the aortic valve. A chest computed tomography (CT) scan was performed in emergency which ruled out an aortic dissection and revealed the presence of an aneurysm of the right sinus of Valsalva. The following day, a transesophageal echocardiogram was performed which confirmed the aneurysm of the right sinus Valsalva and the presence of systodiastolic flow between it and the right ventricular outflow compatible with a fistula. For this reason, the patient was transferred to the Cardiac Surgery Department of another hospital. He underwent cardiac surgery of resection of aneurysmatic tissue, direct suture of the fistula by the combined transaortic / transpulmonary route and reductive plastic surgery of the pulmonary trunk. Aneurysms of sinus of Valsalva are rare cardiac anomalies, which may be either acquired or congenital. A congenital lack of continuity between the aortic media and annulus fibrosis may initiate aneurysm formation. Acquired aneurysms may result from trauma, endocarditis, syphilis, Behcet, Marfan's syndrome and senile–type dilatation. In our case, the etiology of the aneurysm is not well understood. It could be a congenital aneurysm that has fissured over time creating a fistula with the right ventricular outflow. This fistula caused a significant left–to–right shunt resulting in haemodynamic changes such as pulmonary trunk dilation. We report this case because the concomitant presence of an aneurysm of the right Valsalva sinus and a fistula between it and the right ventricular outflow represents an extremely rare and poorly described event in the literature.